2019
DOI: 10.1111/idh.12380
|View full text |Cite
|
Sign up to set email alerts
|

Dental condition and salivary characteristics in Vietnamese patients with chronic kidney disease

Abstract: Objectives To determine the dental status and salivary characteristics and to analyse the correlation between creatinine clearance with DMFT index and salivary flow rate in Vietnamese patients with chronic kidney disease (CKD). Methods This study was conducted on 111 CKD and 109 non‐CKD patients. The socio‐demographic characteristics associated with dental habits and xerostomia status were recorded from a self‐administered questionnaire. Dental status (DT, MT, FT) and salivary characteristics (flow rate; pH; b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
2
5
0
1
Order By: Relevance
“…This lower prevalence of decayed teeth in people with CKD has been reported in other studies, 19,33 and this finding has previously been ascribed to the high salivary urea and phosphate levels in people with CKD. 18,33,40 Even though those end-points were not measured in the current study, the lower prevalence of decayed teeth in those with CKD could be explained by the higher pH environment originating from urea hydrolysis in the saliva, resulting in the neutralization of the end products of bacterial plaque and consequent reduced tooth decay. 18,33,40 People with CKD also presented with a significantly smaller proportion of filled teeth and higher proportion of missing teeth, reflecting the low utilization of curative dental care in the CKD population.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This lower prevalence of decayed teeth in people with CKD has been reported in other studies, 19,33 and this finding has previously been ascribed to the high salivary urea and phosphate levels in people with CKD. 18,33,40 Even though those end-points were not measured in the current study, the lower prevalence of decayed teeth in those with CKD could be explained by the higher pH environment originating from urea hydrolysis in the saliva, resulting in the neutralization of the end products of bacterial plaque and consequent reduced tooth decay. 18,33,40 People with CKD also presented with a significantly smaller proportion of filled teeth and higher proportion of missing teeth, reflecting the low utilization of curative dental care in the CKD population.…”
Section: Discussionmentioning
confidence: 77%
“…18,33,40 Even though those end-points were not measured in the current study, the lower prevalence of decayed teeth in those with CKD could be explained by the higher pH environment originating from urea hydrolysis in the saliva, resulting in the neutralization of the end products of bacterial plaque and consequent reduced tooth decay. 18,33,40 People with CKD also presented with a significantly smaller proportion of filled teeth and higher proportion of missing teeth, reflecting the low utilization of curative dental care in the CKD population. Certainly, in resource-poor public healthcare settings, recommended regular preventive dental care may not be readily accessible.…”
Section: Discussionmentioning
confidence: 77%
“…A different study in Vietnam also found that the DMFT and number of missing teeth in the CKD patients (stage III to V) was significantly higher than the non-CKD group (Pham and Le, 2019). The average age of CKD patients was higher than healthy control and number of missing teeth accounted in the DMFT index was influenced by increasing age (Pham and Le, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have reported alteration in taste in 42% a study on the correlation of kidney function and DMFT index that showed significant positive correlation; however, that was not a good predictive value. In that study, Pham and Le (2019) used the Cockcroft-Gault formula to estimate the creatinine clearance value. However, that formula does not give the best eGFR as what CKD-EPI and MDRD formulas did as Cockcroft-Gault formula is additionally influenced by body weight and BMI (Michels et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…O tratamento para DRC inclui o uso de medicamentos anti-hipertensivos e a baixa ingestão de líquidos, em consequência disso, pode-se ocorrer desidratação e em função desse fato a xerostomia pode se tornar um sintoma frequente e persistente nesses pacientes (Howell;Perry;Patel, 2016;Nascimento et al, 2018;Marinosk et al, 2019;Chiu et al, 2021) 2019) em suas pesquisas notaram que a relação da cárie com o paciente renal crônico é menor que no grupo saudável. Foram sugeridas algumas explicações para esse fato, dentre elas, o alto índice de uréia que afeta o pH bucal, uma maior quantidade de fosfato e uma baixa quantia de cálcio, afetando sua ação no processo de desmineralização e remineralização, consequentemente, aumentando a capacidade tampão exercida pela saliva, assim a doença cárie não terá uma instalação facilitada em comparação aos pacientes saudáveis (Gautam et al, 2014;Tadakamadla et al, 2014;Fregoneze et al, 2015;Swapna;Koppolu;Prince, 2017;Pham;Lee, 2018;Menezes et al, 2019;Silva et al, 2019).…”
Section: Discussionunclassified